A search for star clusters in the outskirts of the Large Magellanic Cloud: indication of clusters in the age gap. Issue 3 (30th September 2020) - Gatto, M; Ripepi, V; Bellazzini, M; Cignoni, M; Cioni, M-R L; Dall'Ora, M; Longo, G; Marconi, M; Schipani, P; Tosi, M
ABSTRACT: The YMCA ( Yes, Magellanic Clouds Again ) and STEP ( The SMC in Time: Evolution of a Prototype interacting late-type dwarf galaxy ) projects are deep g, i photometric surveys carried out with the VLT Survey Telescope (VST) and devoted to study the outskirts of the Magellanic System. A main goal of YMCA and STEP is to identify candidate stellar clusters and complete their census out to the outermost regions of the Magellanic Clouds. We adopted a specific overdensity search technique coupled with a visual inspection of the colour–magnitude diagrams to select the best candidates and estimate their ages. To date, we analysed a region of 23 square degrees in the outskirts of the Large Magellanic Cloud, detecting 85 candidate cluster candidates, 16 of which have estimated ages falling in the so-called age gap. We use these objects together with literature data to gain insight into the formation and interaction history of the Magellanic Clouds.